Lower Levels of Classroom Aggression Predict Stronger Relations Between Peer Victimization and Reactive Versus Proactive Aggression - Morrow, Michael T. (Journal of interpersonal violence, 2022)
We examined the concurrent relations of children?s reactive and proactive aggression with their experience of peer victimization. Extending previous research, we assessed these relations at both the child and classroom levels. We predicted that reactive aggression would relate positively to peer victimization, proactive aggression would relate negatively to peer victimization, and that these relations would vary with classroom levels of aggression. Participants included 1,291 fourth- and fifth-grade children (681 girls; M age = 10.14?years) and their 72 teachers from 9 schools in one public school district in the Mid-Atlantic United States. Children completed self-report measures of peer victimization and teachers completed measures of aggression for each child in their classrooms. Via two-level regression (level 1 = child; level 2 = classroom), reactive aggression related positively to peer victimization and proactive aggression related negatively to peer victimization. The positive relation between reactive aggression and peer victimization was only significant in classrooms with low levels of reactive aggression. The negative relation between proactive aggression and peer victimization was only significant in classrooms with low levels of proactive aggression. Our hypotheses were supported and offered further evidence for differential relations of reactive and proactive aggression with peer victimization at the child level, while demonstrating the important role of classroom norms for aggression in moderating these relations.